In stage pT1 non-muscle-invasive bladder cancer (NMIBC), high KRT20 and low KRT5 mRNA expression identify the luminal subtype and predict recurrence and survival - Breyer, Johannes; Erben, Philipp; Kriegmair, Maximilian (Virchows Archiv, 2017)
Differential expression of cytokeratins (CK) is a characteristic feature of chemoresistant luminal (KRT20) and chemosensitive intrinsic aggressive basal (KRT5) subtypes in muscle-invasive bladder cancer (MIBC). We investigated mRNA expression of KRT5 and KRT20 and its predictive value in stage pT1 bladder cancer. In retrospective analysis of clinical data and formalin-fixed paraffin-embedded tissues (FFPE) of patients with stage pT1 NMIBC who underwent transurethral resection of the bladder, a single-step RT-qPCR was used to measure mRNA expression. Furthermore, immunohistochemical (IHC) staining of CK20, panCK, and MIB1 was performed. Valid measurements were obtained from 231 samples out of a series of 284 patients. Spearman correlation revealed significant associations between mRNA and protein expression of KRT20/CK20 (ρ 0.6096, p < 0.0001) and MKI67/MIB1 (ρ 0.5467, p < 0.0001). A positive correlation was found between MKI67 and KRT20 expression (ρ 0.3492, p < 0.0001), while MKI67 and KRT5 were negatively correlated (ρ −0.1693, p = 0.01). High KRT20 expression (≥40.26) was significantly associated with worse recurrence free survival (RFS) (p = 0.001), progression-free survival (PFS) (p = 0.0003), and cancer specific survival (CSS) (p = 0.0414). The combination of high KRT20 expression and low KRT5 expression (<36.83) was associated with unfavorable RFS (p = 0.0038) and PFS (p = 0.0003) and proved to be the only independent predictor for RFS (p = 0.0055) and PFS (p = 0.0023) in multivariate analysis. KRT20 mRNA determination was superior to CK20 protein estimation with regard to RFS and PFS prediction. KRT20 and KRT5 mRNA quantification can predict recurrence and progression of stage pT1 NMIBC reflecting basal and luminal subtypes of MIBC and is superior to CK20 protein expression determined by IHC.